Estimating a Structural Model of Herd Behavior in Financial Markets - Guarino, Antonio (IMF Working Papers; Working Paper ;, 2010)
We develop a new methodology to estimate the importance of herd behavior in financial markets: we build a structural model of informational herding that can be estimated with financial transaction data. In the model, rational herding arises because of information-event uncertainty. We estimate the model using data on a NYSE stock (Ashland Incorporated) during 1995. Herding often arises and is particularly pervasive on some days. The proportion of herd buyers (sellers) is 2 percent (4 percent) and is greater than 10 percent in 7 percent (11 percent) of information-event days. Herding causes important informational inefficiencies, amounting, on average, to 4 percent of the expected asset value.